Visualization of facet-dependent pseudo-photocatalytic behavior of TiO2 nanorods for water splitting using In situ liquid cell TEM. (August 2019) - Yin, Zu-Wei; Betzler, Sophia B.; Sheng, Tian; Zhang, Qiubo; Peng, Xinxing; Shangguan, Junyi; Bustillo, Karen C.; Li, Jun-Tao; Sun, Shi-Gang; Zheng, Haimei
Abstract: We report an investigation of the pseudo-photocatalytic behavior of rutile TiO2 nanorods for water splitting observed with liquid cell transmission electron microscopy (TEM). The electron beam serves as a "light" source to initiate the catalytic reaction and a "water-in-salt" aqueous solution is employed as the electrolyte. The observation reveals that bubbles are generated preferentially residing near the 110 facet of a rutile TiO2 nanorod under a low electron dose rate (9.3–18.6 e - /Å 2 ·s). These bubbles are ascribed to hydrogen gas generated from the pseudo-photocatalytic water splitting. As the electron beam current density increases to 93 e - /Å 2 ·s, bubbles are also found at the 001 and 111 facets as well as in the bulk liquid solution, demonstrating the dominant effects of water electrolysis by electron beam under higher dose rates. The facet-dependent pseudo-photocatalytic behavior of rutile TiO2 nanorods is further validated using density functional theory (DFT) calculation. Our work establishes a facile liquid cell TEM setup for the study of pseudo-photocatalytic water splitting and it may also be applied to investigation of other photo-activated phenomena occurring at the solid-liquid interfaces. Graphical abstract: Photocatalytic water splitting using TiO2 as the active catalyst has been studied intensively. Although facet-dependent photocatalytic properties of TiO2 nanostructures was speculated, it has not been directly observed. Here, we visualized the facet-dependent pseudo-photocatalytic water splitting using a liquid cell TEM setup. Using a low dose electron beam as the "light" source and a "water-in-salt" aqueous solution, the preferential hydrogen bubble generation near the 110 facets of a TiO2 nanorod was observed.Image 1 Highlights: Established a facile liquid cell TEM setup for in situ study of "photo" catalytic water splitting. The generated H2 bubbles preferentially reside near the 110 facets of a rutile TiO2 nanorod. The electron beam was used as a "light" source to initiate the catalytic water splitting. A "water-in-salt" solution and low electron dose suppressed direct water electrolysis by e-beam. A lower work function of the TiO2 110 facets from DFT calculations validates the observation.